1999
DOI: 10.1590/s1516-35981999000300026
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de novilhas leiteiras alimentadas com dietas à base de Cana-de-açúcar

Abstract: O objetivo deste trabalho foi avaliar o comportamento ingestivo de novilhas mestiças Holandês x Zebu alimentadas com dietas à base de cana-de-açúcar suplementadas com fontes de nitrogênio não-protéico [NNP] (uréia e cama de frango, em substituição parcial da uréia) e, ou, adição de probióticos (sem probiótico, com levedura ou com microbiota ruminal). Vinte e quatro novilhas, com idade e peso médio inicial de 15 meses e 247 kg, respectivamente, foram mantidas em baias individuais e alimentadas à vontade, durant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
32

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 8 publications
3
7
0
32
Order By: Relevance
“…This result confirms the ones reported by Miranda et al (1999), who observed that the addition of probiotics such as yeast did not influence these activities. Some studies report that the time of chews per ruminal bolus can be reduced as the animals increase the efficiency in the reduction of the size of particles per unit of time by reducing time interval between the ruminal boluses or by increasing the rate of mandibular movements/ hour (Bae et al, 1981;Deswysen et al, 1987).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result confirms the ones reported by Miranda et al (1999), who observed that the addition of probiotics such as yeast did not influence these activities. Some studies report that the time of chews per ruminal bolus can be reduced as the animals increase the efficiency in the reduction of the size of particles per unit of time by reducing time interval between the ruminal boluses or by increasing the rate of mandibular movements/ hour (Bae et al, 1981;Deswysen et al, 1987).…”
Section: Resultssupporting
confidence: 92%
“…These results emphasize the assumption that the animals are conditioned to go for the feed at the time it is offered (Jaster & Murphy, 1983). According to the literature, the probability of the animal being or staying in its feeding activity reaches its maximum value immediately after feed is offered, since it is fresh (Damasceno et al, 1999Miranda et al, 1999.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Queiroz et al (2001) verificaram que o horário de fornecimento da ração ocasionou diferença nas características de ingestão, com o tempo despendido em ingestão maior quando o alimento foi fornecido pela manhã. Miranda et al (1999), estudando o comportamento alimentar de novilhas, observaram que a maior porção de consumo ocorreu durante o dia, uma vez que o consumo de MS foi maior após o fornecimento de alimentação fresca e a ruminação ocorre preferencialmente à noite, quando a temperatura ambiental é mais amena, o que também foi observado neste trabalho.…”
Section: Variávelunclassified
“…Sugar cane without calcium hydroxide provided the highest NCB (P<0.10), whereas, when it was added to calcium hydroxide, the values of NCB were reduced. Miranda et al (1999) evaluated the feeding behavior of dairy heifers fed diets based on sugar cane and found no difference in time spent eating, ruminating and total chewing time, in minute/day for heifers fed different sources of NPN and probiotics.…”
Section: Itemmentioning
confidence: 99%